2020
DOI: 10.1299/jamdsm.2020jamdsm0098
|View full text |Cite
|
Sign up to set email alerts
|

Method of designing gear-honing-wheel geometries (Validation based on fundamental theory and honing experiments)

Abstract: The present paper describes a method for determining geometries of gear-honing wheels used in the final process for manufacturing automotive transmission gears. Inappropriate geometries of gear-honing wheels could cause large undulations on finished gear-tooth flanks, and the finished gear would be out of the required accuracy. In such cases, the geometries of gear-honing wheels are required to be modified iteratively until the finished gears have sufficient accuracy. The change in meshing stiffness of a gear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Among these parameters, the honing wheel and the target gear share the same normal pressure angle and normal module. In addition, the authors have previously shown that tooth-flank undulations can be improved by achieving a suitable meshing stiffness balance between the honing wheel and the target gear as a result of applying a profile shift coefficient that obtains zero meshing phase difference between the right and left tooth flanks (Matsuo et al, 2020). However, there have been cases where, depending on the target gear geometries involved, early changes have occurred in micro geometries, thereby drastically shortening the honing wheel tool life in mass production.…”
Section: Proposed Honing Wheel Design Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these parameters, the honing wheel and the target gear share the same normal pressure angle and normal module. In addition, the authors have previously shown that tooth-flank undulations can be improved by achieving a suitable meshing stiffness balance between the honing wheel and the target gear as a result of applying a profile shift coefficient that obtains zero meshing phase difference between the right and left tooth flanks (Matsuo et al, 2020). However, there have been cases where, depending on the target gear geometries involved, early changes have occurred in micro geometries, thereby drastically shortening the honing wheel tool life in mass production.…”
Section: Proposed Honing Wheel Design Methodsmentioning
confidence: 99%
“…We proposed a method of analysis the tooth flank in internal gear honing in which machining proceeds under linecontact meshing in our previous study (Matsuo et al, 2020). This analysis method is described here for the purpose of calculating the relative sliding velocities of the target gear tooth flank.…”
Section: Analysis Tooth-flank Micro Geometry In Internal Gear Honingmentioning
confidence: 99%
See 3 more Smart Citations